Energy Relations between Russia and China: Playing Chess with the Dragon - Henderson, J; Mitrova, T (Oxford Institute for Energy Studies, 2016)
This paper addresses the expanding energy cooperation between Russia and China in the context of the political and commercial relationship between the two countries. It assesses progress during the post-Soviet era, but focuses especially on the past two years since sanctions were imposed on Russia by the US and the EU. It attempts to analyse the balance of bargaining power between the two countries via a detailed analysis of the various oil, gas, coal and power sector deals that have taken place, and assesses whether Russia’s pivot to Asia is moving as smoothly as had been hoped by the Kremlin when the first major gas export deal with China was signed in May 2014. The paper continues the series of analyses of Russia’s hydrocarbon export strategy that has been published over the past two years, and also deepens the OIES output on China and its energy import strategy. Furthermore, it aims to contribute to an understanding of the balance of Russia’s political and commercial ambitions, which is of vital relevance to any analysis of the country’s future relations with the global energy economy.